Emissions from charging electric vehicles in the UK. (September 2022) - Mehlig, Daniel; ApSimon, Helen; Staffell, Iain
Graphical abstract: Abstract: Understanding how to best integrate electric vehicles (EVs) into electricity systems is key to the success of both sectors. We pair national-scale EV charging data with high resolution electricity generation data for the UK to calculate the average and marginal emissions produced through charging EVs. Considering the average generation mix weighted by when charging occurs, a typical Battery EV (BEV) emitted 41 g CO2, 27 mg NOx and 0.7 mg PM2.5 per kilometre in 2019. A static analysis using annual averages underestimates these values by 4 %. The 'marginal' emissions from BEV charging are 25 % higher than average emissions for CO2 and NOx, and 50 % lower for PM2.5 . Smart charging was found to reduce average CO2 emissions by 10 % when compared to the typically charged vehicle; however, smart charging strategies may increase marginal emissions. Future smart charging strategies should minimise marginal emissions and will require access to 24-hour opportunistic smart charging.